2004
DOI: 10.1111/j.1365-2222.2004.02002.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of asthma and allied diseases among active adolescent tobacco smokers after controlling for passive smoking exposure. A cause for concern?

Abstract: Being asthmatic or allergic does not seem to act as a deterrent towards starting active smoking or continuing to smoke in adolescence. Results suggest the need for considering individual allergic status in programming health educational activities aimed at reducing smoking among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 29 publications
6
56
3
Order By: Relevance
“…Epidemiologic, laboratory, and clinical studies clearly demonstrate that cigarette smoking is a risk factor for the development of Th-2-mediated diseases like asthma (5,6,(37)(38)(39)(40)(41). The ability of DCs to generate Th-1 or Th-2 immunity is regulated by many factors, including Ag type and dose, the level of costimulatory molecules expressed, the presence of polarizing cytokines and other mediators, and the presence of innate receptor stimulants at the time of Ag exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic, laboratory, and clinical studies clearly demonstrate that cigarette smoking is a risk factor for the development of Th-2-mediated diseases like asthma (5,6,(37)(38)(39)(40)(41). The ability of DCs to generate Th-1 or Th-2 immunity is regulated by many factors, including Ag type and dose, the level of costimulatory molecules expressed, the presence of polarizing cytokines and other mediators, and the presence of innate receptor stimulants at the time of Ag exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the relationship between tobacco smoking and the prevalence of rhinitis (55, 715,[723][724][725][726][727][728][729]. In three studies, the prevalence of self-reported nasal allergy symptoms was lower in smokers than in nonsmokers (55,715,723).…”
Section: Pollutantsmentioning
confidence: 99%
“…In three studies, the prevalence of self-reported nasal allergy symptoms was lower in smokers than in nonsmokers (55,715,723). In one study involving adolescents, smoking was found to increase the prevalence of rhinoconjunctivitis (729). On the other hand, there was no effect of environmental tobacco smoke (ETS) exposure at home, neither on allergic sensitization nor allergic rhinitis (730).…”
Section: Pollutantsmentioning
confidence: 99%
“…Population studies are hampered by cross-sectional and case-control study design, the use of poor measures of tobacco smoke exposure and, due to their reliance on selfreport measures or questionnaires, the potential for inaccuracies in the diagnosis of asthma as a result of recall bias. Nevertheless, the overall patterns of results indicate a higher prevalence of asthma particularly among female smokers compared to female nonsmokers (table 1) [6][7][8][9]. For example, the Canadian National Population Health Survey [7] reported that female smokers had a 70% higher prevalence rate of asthma compared to nonsmokers, and the interaction between smoking and sex was particularly evident among females aged ,25 yrs (OR 2.18) and among heavier as compared to lighter smokers or nonsmokers.…”
Section: Smoking As a Risk Factor For The Development Of Asthmamentioning
confidence: 99%
“…It is now recognised, however, that classification by disease severity simply suggests a static feature, which is clearly not the the interaction between smoking and sex is particularly evident among heavier smokers compared to lighter smokers or nonsmokers [6][7][8][9][10][11][12][13][14] Incident asthma Smoking is highly predictive of the development of new onset asthma in allergic adults with a clear dose-response effect of smoking exposure [15] Increased asthma morbidity and mortality Asthmatic smokers are at risk of developing more severe symptoms, higher frequency of exacerbations, and worse asthma-specific quality of life [16][17][18][19][20][21]; cigarette smoking in asthma is also associated with increased numbers of life threatening asthma attacks and greater asthma mortality [22,23] Greater asthma severity Smoking status and smoking duration are strongly related in a dose-dependent fashion to the level case in everyday clinical asthma where the level of severity varies in relation to the amount of anti-asthma medication taken. These considerations have promoted the more clinically informative concept of asthma control [52,53].…”
Section: Clinical Outcomes In Smokers With Asthmamentioning
confidence: 99%